Gambaran Pola Makan Lansia Obesitas dengan Hipertensi di Wilayah Kerja Puskesmas Tegalrejo Kota Salatiga - Kristiawan P.A. Nugroho; Junet Franzisca da Costa; Rambu L.N.K. Retno Triandhini; Stefani Ratna Indriati (Journal of Health (JoH), 2019)
Background: Obesity is one of the problems of non-communicable diseases that are still commonly found. Indonesia is one of the developing countries with high levels of obesity. Based on the Central Java Health Profile of 2015, the highest prevalence of obese population is found in Salatiga. Obesity increases the risk of high blood pressure or hypertension. Elderly are age group that can be obese and hypertension. Problems of Obesity and Hypertension can occur in the elderly can be caused by the wrong diet. Objective: The study was conducted to examine the diet of elderly people with obesity with hypertension in the work area of puskesmas Tegalrejo. Method: This research method using descriptive quantitative. The elderly respondents aged> 50 years were selected based on secondary data from Tegalrejo Puskesmas with IMT calculation and hypertension identified. Data collection with structured interview using questionnaires, FFQ sheet feeding, and Food Recall. This research was carried out in February-April 2018. Data analysis includes questionnaire results from question items provided, then analyzed descriptively; the FFQ and Food Recall sheets were analyzed to obtain data on the types of foods routinely consumed within the observation period of the study, the frequency, the number of doses, the method of processing, and the calculation of nutrients and calories. Result: Based on FFQ and Food recall fall into the category of deficit but based on anthropometry into more categories that affect diet. Conclusion: Elderly diet obesity and hypertension tend to be less good and there are other factors that influence diet.